PENGARUH FAKTOR KEPERILAKUAN ORGANISASI TERHADAP KINERJA INDIVIDUAL DENGAN PENGGUNAAN SISTEM INFORMASI KEUANGAN DAERAH (SIKD) SEBAGAI VARIABEL INTERVENING (Studi Pada SKPD di Kabupaten Agam) - Fadhli Irsyadi; Yusralaini -; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted to examine the influence of organizational factors; management support, the clarity of objectives, and training toward the individual performance with the use of Local Information Financial System as the intervening variable. The data were collected by sending 100 questionnaires to the user of Local Information Financial System (SIKD) in Agam regency, in which only 60 questionnaires were given back to the researcher. The statistics method used to examine each of the hypotheses is path analysis by using SPSS 17.0. From ten hypotheses, six hypotheses; H1, H3, H5, H7, H8, H10. It shows that the clarity of objectives, and training positively give the direct influence toward SIKD, whereas the management support does not affect the SIKD. This research also show that the clarity of objectives and SIKD positively affect the individual performance, while management support and training do not affect the individual performance. If the independent and dependent variables are mediated by the use of Local Information Financial System, it shows that management support and training indirectly affect the individual performance with the use of Local Information Financial System (SIKD) as the intervening variable.Keywords: behavioral, organizational, performance and information financial